Karakter Fisik Dan Aktivitas Antibakteri Sabun Padat Ekstrak Kulit Pisang Mas (Musa Acuminata Colla) Terhadap Staphylococcus Aureus - Darsini; Desi Sri Rejeki; Endang Istriningsih; Setyo Wulandari, Prihastini (PT. Pubsains Nur Cendekia, 2025)
Solid soap is a type of skin cleanser formulation that functions to remove dirt, oil, and microorganisms such as bacteria. This study aims to formulate a solid bath soap containing ethanol extract of